2021
DOI: 10.1007/s11426-021-1103-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen vacancies in metal oxides for rechargeable ion batteries

Abstract: Rechargeable ion batteries are one of the most reliable energy storage technologies for the applications ranging from small portable devices and electric vehicles to renewable energy integration and large-scale stationary energy storage. In the roadmap of developing and understanding new electrode materials for rechargeable ion batteries, oxygen vacancies, known as defects in metal oxides, have shown a high impact on the final electrochemical performance of the oxides. The present review aims to summarise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 156 publications
(207 reference statements)
0
28
0
Order By: Relevance
“…The ESR resonance signal at g = 2.004 can be attributed to free electrons trapped by OVs. [35,50] Furthermore, the enhancement of ESR signal intensity indicates the increase of oxygen concentration. It can be seen that the content of OVs increases with increasing pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ESR resonance signal at g = 2.004 can be attributed to free electrons trapped by OVs. [35,50] Furthermore, the enhancement of ESR signal intensity indicates the increase of oxygen concentration. It can be seen that the content of OVs increases with increasing pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, laser bombardment and plasma treatment can also create oxygen vacancy defects in the material. [34,35] Recently, Zhang et al indicated that the energy level barrier of OVs can be reduced under the action of strain. [36] Inspired by this, we considered whether OVs could be introduced during material synthesis under high pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to the x-ray spectroscopy techniques, resolution of x-ray diffraction is usually too low to detect light-induced V O , but x-ray photoelectron spectroscopy (XPS) [12, 13, 22-24, 30-34, 36-42, 71-73] and x-ray absorption spectroscopy (XAS) [1,2,24,27,33,46,50,54,60,62,63,65,71,74] are effective. XAS, including x-ray absorption near-edge structure spectroscopy and extended x-ray absorption fine structure, could assess oxidation state in bulk and average coordination environment of elements in materials.…”
Section: Measurements Of Light-induced V Omentioning
confidence: 99%
“…[35][36][37] Moreover, oxygen vacancies can effectivity reduce the Li + diffusion barrier and afford extra active sites, which are beneficial in enhancing the electrochemical properties of the electrode materials. [38][39][40][41] Cao et al designed Ni/MoO 2−σ nanospheres with rich oxygen vacancies, which show outstanding rate capability and superior discharge specific capacity due to the atomic level oxygen vacancies. 41 Although the high rate capability and cyclic performance of MoO 2 could be efficiently improved by the above strategies (heterostructure or oxygen vacancies), the research studies on introducing both heterostructure and oxygen vacancies to regulate the electronic structure and enhance the intrinsic electronic conductivity and Liion diffusion kinetics for LIBs are still insufficient.…”
Section: Introductionmentioning
confidence: 99%